Interaction of Molybdenum With Trypsin and Pepsin by Dialysis Equilibrium Method - SINGH, R.P.; CHAUDHARY, R.; RANI, RITU; KUMAR, S.; ARORA, S.K. (Asian Journal of Chemistry, 2010)
The binding of molybdenum with trypsin and pepsin enzymes has been studied using dialysis equilibrium technique. The effect of pH and temperature on the anion binding behaviour has been explained in the light of protonation and deprotonation behaviour of the two enzymes. The differences in binding behaviour has been attributed to large differences in their cationic groups contents. The binding constants, viz. intrinsic association constants (K) and binding sites (n) were determined from Scatchard’s plots. The linear nature of plots under similar conditions of pH and temperature in two cases is an indication of the involvement of a single one class of sites. The pH dependence of anion binding exhibited the involvement of cationic groups in the interaction. The nearly similar values of free energy and entropy changes for trypsin and pepsin is an index of their similar anion binding capacity. The enthalpy and entropy changes at pH 5.50 provided evidence for covalent linking between molybdenum and enzyme groups.